ANALISIS ATRIBUT PEMASARAN PADA BEBERAPA RESTORAN CEPAT SAJI DI JAKARTA - Chandra Adhitya Manoppo; Edi Abdurachman (Bina Nusantara University, 2009)
The purpose of this research is to find whether marketing attributes of some fast food restaurants have met with consumer’s expectations, and identify and analyze the correlations between demography (gender, age, education, job, expenditure per month, frequency of eating-out, and marital status) and the marketing attributes (product, price, service, promotion, and place) from fast food restaurant. The methodology used in this research is conducting a literature study and collecting primary data by using survey method with questionnaire. The respondents were 120. The result of this research covers 4 important points. First of all, the product, price and place are found to be related to the amount of expenditure per month, the frequency of eat-outs, and marital status. Secondly, service is related to age, job, the amount of monthly expenditure and marital status. Next, the promotion is related to age and job. These three outcomes indicate a need for marketing innovation based on the relations between the demography and the marketing attributes from fast food restaurants. Lastly, the performance of some fast food restaurants at promotion and place attributes has fulfilled consumer expectation. Even, for some fast food restaurants, the attribute of place has overly fulfilled the consumer’s expectation. Therefore, the promotion and place attributes should be maintained well. However, the attributes of price, product, and service have not met with the consumer’s expectation, and thus, there is a need to improve the performance of the fast food restaurants in order to always fulfilled the consumer’s expectation.